The Study Of Consumer Acceptance On Catfish (Pangasius hypophthalmus) Ball Added With Katuk (Sauropus androgynus) Leaves As A Colour Additive - Apri Listari; Syahrul '; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate consumer acceptance on catfish ballwhich added with katuk leaves as a colour additive. Four types of catfish ballwere made from a mixture of catfish, sago flour, tapioca flour, seaweed, egg,spices (onion, garlic, pepper powder, salt) and each catfish ball added with katukleaves at a level of 0%, 5%, 10% and 15% as a colour additive. Catfish ball wasevaluated for consumer acceptance, proximate composition and bacterial total.The result showed that catfish ball which added with 10% of katuk leaves was thebest in sensory quality. Protein, fat, moisture, ash and bacterial total of the bestcatfish ball was 13.51%, 0.75 %, 70.85% , 0.89% and 3,6 x 102 colonies/grespectively.Keywords: Acceptance, katuk leaves, catfish ball, colour additive